대학에서의 사회적 지지와 직업 가치관, 진로 결정수준, 삶의 질 간의 영향 관계 연구: 디자인 분야 전공 대학생을 중심으로 - 이희영(Hee-Young Lee) (한국콘텐츠학회 논문지, 22(1), 2022)
This research was conducted to investigate the structural relationship social support of college students has with their occupational values, career decision, and quality of life. Subjects of study were art and design college students in Seoul. Social support, occupational values, career decision, and quality of life were measured as criteria. SPSS and AMOS were used to test structural model and the relationship among variables. Results of this study are as follows. First, effects of social support on internal and external occupational values were studied. Second, effects of social support on quality of life-satisfaction and happiness-were studied. Third, effects of occupational values on career decision standards were studied. External occupational values had a statistically significant correlation with career decision, while internal occupational values were found to have no statistically significant effect on career decision. Based on the results, it can be inferred that colleges which need to support the careers and employment of students must support students with informational and instrumental support. Design students must be provided with proper career coaching and environment improvement, as well as development of programs suitable for various talents and aptitudes, so that they can shape appropriate occupational values. 본 연구는 대학생들에 대한 대학에서의 사회적 지지가 직업 가치관, 진로 결정, 삶의 질에 어떠한 영향을 미치는지 그 구조적 관계를 검증하기 위해 수행되었다. 연구 대상은 디자인학과에 재학 중인 대학생이었다. 측정 도구는 사회적 지지 척도, 직업 가치관 척도, 진로 결정 척도, 삶의 질 척도였고, 수집된 자료는 SPSS 및 AMOS 프로그램을 통하여 구조모형 검증 및 변수 간의 영향 관계를 검증하였다. 본 연구의 결과는 다음과 같다. 첫째 사회적 지지를 구성하는 요인 중 내재적 직업 가치관과 외재적 직업 가치관으로 구성된 영향에서 정보적 지지, 물질적 지지가 유의한 정(+)의 영향을, 그리고 정서적 지지는 부(-)의 영향을 미치는 것으로 나타났다. 둘째, 사회적 지지가 만족감과 행복감으로 구성된 삶의 질에 미치는 영향에서는 정보적 지지, 물질적 지지가 만족감과 행복감 모두에 정(+)의 영향을, 그리고 정서적 지지는 부(-)의 영향을 미치는 것으로 나타났다. 셋째, 직업 가치관이 진로 결정수준에 미치는 영향에 있어서 외재적 직업 가치관은 정(+)의 영향을 미치는 것으로 보였으나, 내재적 직업 가치관은 유의한 영향을 미치지는 않는 것으로 분석되었다. 이러한 결과를 바탕으로 정보적 지지와 물질적 지지를 학생들에게 지원하고 대학생의 올바른 진로 지도 및 환경 개선 그리고 다양한 소질과 적성에 맞는 프로그램의 개발이 수반되어야 할 것이다.